Herbal medicine research and global health: an ethical analysis - Jon C Tilburt; Ted J Kaptchuk (The World Health Organization, 2008)
Governments, international agencies and corporations are increasingly investing in traditional herbal medicine research. Yet little literature addresses ethical challenges in this research. In this paper, we apply concepts in a comprehensive ethical framework for clinical research to international traditional herbal medicine research. We examine in detail three key, underappreciated dimensions of the ethical framework in which particularly difficult questions arise for international herbal medicine research: social value, scientific validity and favourable risk-benefit ratio. Significant challenges exist in determining shared concepts of social value, scientific validity and favourable risk-benefit ratio across international research collaborations. However, we argue that collaborative partnership, including democratic deliberation, offers the context and process by which many of the ethical challenges in international herbal medicine research can, and should be, resolved. By "cross-training" investigators, and investing in safety-monitoring infrastructure, the issues identified by this comprehensive framework can promote ethically sound international herbal medicine research that contributes to global health.